Interlink between Tunable Material Properties and Thermoresponsiveness of Cross-Linked Poly(N-vinylcaprolactam) Thin Films Deposited by Initiated Chemical Vapor Deposition - Muralter, Fabian (Macromolecules, 2019)
[Image: see text] In this contribution, we report on the thin-film synthesis of a novel thermoresponsive polymer, namely, poly(N-vinylcaprolactam) cross-linked by di(ethylene glycol)divinyl ether [p(NVCL-co-DEGDVE)] by initiated chemical vapor deposition (iCVD). Its transition between swollen and shrunken states in film thickness and the corresponding lower critical solution temperature (LCST) was investigated by spectroscopic ellipsometry in water. Water contact angle measurements and nano-indentation experiments reveal that the transition is accompanied by a change in wettability and elastic modulus. The amount of cross-linking was used to tune the thermoresponsive behavior of the thin films, resulting in higher swelling and LCST, increased surface rearrangement, and lower stiffness for less cross-linked polymers. For the first time, the filament temperature during iCVD synthesis was used to vary the chain length of the resulting polymeric systems and, thus, the position of their thermoresponsive transition. With that, swelling of up to 250% compared to the dry thickness and transition temperatures ranging from 16 to 40 °C could be achieved.